2013
DOI: 10.1007/s11356-013-2020-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary toxicological assessment of phthalate esters from drinking water consumed in Portugal

Abstract: This paper reports, for the first time, the concentrations of selected phthalates in drinking water consumed in Portugal. The use of bottled water in Portugal has increased in recent years. The main material for bottles is polyethylene terephthalate (PET). Its plasticizer components can contaminate water by leaching, and several scientific studies have evidenced potential health risks of phthalates to humans of all ages. With water being one of the most essential elements to human health and because it is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 23 publications
0
18
3
Order By: Relevance
“…The results also showed that the total non-carcinogenic risk of DEP and DEHP was lower than 1, indicating that there would be unlikely incremental non-carcinogenic risk to humans. Both carcinogenic and non-carcinogenic risks of PAEs in drinking water to female were slightly higher than those to male (37). Based on the results of the present study, the risk of fungal infections in lactating women due to phthalates of DHEP and di-butyl phthalate in water with values of 0.05 and 0.008 μg/kg/d, respectively, was higher than that in other groups.…”
Section: Discussioncontrasting
confidence: 37%
“…The results also showed that the total non-carcinogenic risk of DEP and DEHP was lower than 1, indicating that there would be unlikely incremental non-carcinogenic risk to humans. Both carcinogenic and non-carcinogenic risks of PAEs in drinking water to female were slightly higher than those to male (37). Based on the results of the present study, the risk of fungal infections in lactating women due to phthalates of DHEP and di-butyl phthalate in water with values of 0.05 and 0.008 μg/kg/d, respectively, was higher than that in other groups.…”
Section: Discussioncontrasting
confidence: 37%
“…DBP as an environmental contaminant and its exposure from food containers is of concern as it represents a risk to reproductive and developmental toxicity (23,24).…”
Section: -H Exposurementioning
confidence: 99%
“…[23][24][25] In addition, phthalates have been detected from various air 26 and water samples, such as river water and tap water. 19,27,28 The Ministry Health, Labour and Welfare Japan has established reference values for dibutyl phthalate (DBP) of 10 μg L -1 and di(2-ethylhexyl)phthalate (DEHP) of 80 μg L -1 , respectively, in tap water (drinking water), 29 and the World Health Organization has established a drinking water guideline for DEHP to be 8 μg L -1 . 30 In this study, a novel extraction capillary that is packed with a CO2 laser supersonic drawing PET nanofiber sheet was developed.…”
Section: Introductionmentioning
confidence: 99%